Modifying Polyvinylidene Chloride Resin with Fluorine Monomer and Cross‐Linking Monomers - Gao, Fengjun; Zhang, Zhifeng; Song, Qianqian; Abo‐Dief, Hala M.; Alzahrani, Eman; Wang, Shouyang; Liu, Yan; Shao, Qian; Yang, Jing; Guo, Zhanhu; El‐Bahy, Zeinhom M.; Ge, Ruixiang (Macromolecular rapid communications., 2024)
Modified polyvinylidene chloride (PVDC) resin was prepared using octafluoropentyl methacrylate and trimethylolpropane trimethacrylate as modifying monomers through seeded emulsion polymerization. The successful incorporation of octafluoropentyl methacrylate into the PVDC resin was confirmed by Fourier transform infrared spectroscopy (FTIR) and X‐ray photoelectron spectroscopy (XPS) analyses. Scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and XPS were utilized to investigate the element distribution in the modified monomer emulsion and the mechanism of monomer modification. The results demonstrated that the fluorine monomer was reacted in the resin, and mainly concentrated on the surface of the resin. The addition of octafluoropentyl methacrylate and trimethylolpropane trimethacrylate improved the water resistance of the resin. Compared to unmodified PVDC resin, the contact angle of the modified PVDC resin increased from 89.46° to 109.51°, and the water resistance at room temperature increased from 120 to 500 h. Furthermore, the modified resin exhibited excellent mechanical properties, thermal stability, and storage stability. The polyvinylidene chloride resin was modified with fluorine monomer and cross‐linking monomers to achieve enhanced properties.